Le Financement Des Pme « Africaines » : La Nécessité Du Crédit-Bail Et La Bourse Des Valeurs - Pony Lucas (European Scientific Journal, ESJ, 2016)
Confronted with the growing scarcity of resources in the global scale, the international political dialogue, in accordance with the Monterry consensus (2002) and the Doha conference (2008), recommends the reinforcement of internal resources mobilization in developing countries to achieve the Millennium Development Goals. In the case of Cameroon, emphasis is put on leasing as a form of financing, so as to enable a company to acquire production equipment; that is, goods that will enhance production in a company. Moreover, the financing of SME centered on the stock exchange speculations as possible alternatives of long-term SME financing, i.e. for more than five years and based on tangible fixed assets, can be an orientation to the fight against poverty in Africa. To succeed, the main objective of this study consist of evaluating the leasing performance between 1994 and 2008 practiced in cameroonian banking system, following the 2007-2008 economic and financial world crisis. What will not be possible without insisting on the Durban Watson test for the period of 1994-2008; thus, evaluating the role of leasing and the Stock Market in the SME financing. The present study identifies suitable strategies to improve the output and the effectiveness of leasing. In addition, investigations will lead to results that can contribute to decrease the bank loan application shares rejected by the banks in short and long periods; the stock market will take over. The methodological approach will focus on data collection, statistical and econometric analysis which estimates the output and the performance of leasing in development, financing and poverty in Cameroon. The recommendations will reinforce the Cameroon banks’ capacities to finance development and the fight against poverty by leasing.